Analisis Usaha Kecil Menengah Rumah Makan Padang - Khairil Azmi; Muhammad Jamil; Faeza Rezi S (Jurnal Manajemen Riset Inovasi, 2024)
Currently, competition in the world of work is getting tougher and unemployment is increasing. Forcing the government to immediately overcome unemployment by expanding job opportunities is impossible. Unemployment does not only come from people who do not have expertise in certain fields but also from employees who are retired early by companies, both large and small companies. Thus, you can imagine how many Indonesians do not have jobs. In this case there must be awareness from the whole community to play an active role in overcoming unemployment because the government only helps with government programs such as UKM (Small and Medium Enterprises). When running a small and medium business, you need a business analysis so that the business can run well, one of these businesses is a Padang restaurant. The aim of the research is to analyze small and medium Padang restaurant businesses. This research uses qualitative methods and is classified as field research with semi-structured interviews and documentation as data collection techniques. The findings from this research are that there are several things that need to be improved in managing a Padang restaurant business, including: the quality of the food must remain stable, the taste of the employees is friendly, the business premises are clean, prayer places must be provided and so on.